Political and religious identities of British evangelicals - Hatcher, Andrea C. (Cham, Switzerland Palgrave Macmillan, 2017)
The same, but different -- A view from the top -- Religious and political identities -- Political engagement -- Cultural engagement -- Toward and evangelical identity -- Appendices: Sample instrument for elite interviews ; Survey for focus groups ; Descriptive statistics of focus group participants.
"The book examines the paradoxical relationship between the religious and political behaviors of American and British Evangelicals, who exhibit nearly identical religious canon and practice, but sharply divergent political beliefs and action. Relying on interviews with British religious and political elites (journalists, MPs, activists, clergy) as well as focus groups in ten Evangelical congregations, this study reveals that British Evangelicals, unlike their American counterparts known for their extensive involvement in party politics, have no discernible ideological or partisan orientation, choosing to pursue their political interests through civic or social organizations rather than electoral influence. It goes further to show that many British Evangelicals shun the label itself for its negative political connotations and in-/out-group sensibility, and choose to focus on a broader social justice imperative rendered almost incoherent by a lack of group identity. Placing itself at the forefront of an incipient but growing segment of comparative research into the intersectionality of religion and politics, the work satisfies a lacuna of how the same religious tradition can act differently in public squares contextualized by political and cultural variables. --
Includes bibliographical references and index
Keywords: Evangelicalism -- Great Britain -- History -- 21st century; Evangelicalism -- Political aspects -- Great Britain; Identification (religion); Christianity and politics -- Great Britain; Christianity and culture -- Great Britain; Christianity and culture; Christianity and politics; Evangelicalism; Evangelicalism ; Political aspects; History; Great Britain